Reflections on the justice of the victims - Reyes Mate, Manuel (Estudios de Filosofía, 2008)
What is meant by this is that reality should not be confused with factuality: facticity is the part of reality that has come to be, that has triumphed. "Das Wesen ist das Ge-wesene". But what memory says is that what wanted to be and could not, unrealized dreams, those fallen into the gutters of history, is also part of reality. Adorno, says a good connoisseur of it, José Antonio Zamora, expresses this idea in a precise and provocative formula: "making suffering speak is the condition of all truth." The truth is not aseptic, timeless, abstract, but a judgment from the experience of suffering. [Fragment]